The Effect Of Family Gathering On Increasing The Psychological Well Being Of The Elderly In Nursing Home: Pengaruh Family Gathering Terhadap Peningkatan Kesejahteraan Psikologis Lansia DiPondok Lansia - Nurmayunita, Heny; Zakaria, Amin (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2023)
ABSTRACT Background:The ability of coping mechanisms is greatly decreased resulting in the elderly easily experiencing psychological well-being problems. The elderly who are far from their families are in old age huts or nursing homes, often feel they are not needed anymore,are left out or thrown away from their families and are compounded by problems with illnesses that don't go away. There are several ways to improve the psychological well-being of the elderly, one of which is to provide social support through family gathering activities Purpose:This study aims to analyze the effect of family gatherings on the psychological well-being of the elderly at Pondok Lansia Al-Islah Malang. Methods:The research design used was a one-group pre-post test design pre-experimental on a population of 23 elderly people at Pondok Lansia Al-Islah Malang, using a total sampling approach. Data collection was carried out in June 2022, namely before and after giving the family gathering treatment, using the Scale of Psychological Well-Being (SPWB)questionnaire. The data normality test used the One-Sample Kolmogorov-Smirnov Test and to analyze the effect of family gathering on the psychological well-being of the elderly used the Paired T-Test on pre and post-test data with the help of the SPSS21 application Result: The results show that family gatherings have an influence on the psychological well-being of the elderly at Pondok Al-Islah with a significance value of 0.034 which is less than 0.05. Family gatherings can improve the quality of mental health, increase self-confidence, prayer, enthusiasm or encouragement, advice and acceptance, so that it meets the expectations of the elderly. Conclusion: The family gathering program can be used as a routine activity and becomes acommitment between the family and the management from the start to entrust their elderly Keyword: Family Gathering, Psychological Well-Being, Elderly